Recognition of the fossil fauna and flora of the Cretaceous of the paleontology cabinet of the EAP of Geological Engineering of the UNMSM - Aldana Álvarez, Manuel (2013)
The Cabinet of Paleontology of the E.A.P. Geological Engineering contains a large number of whole and fragmented fossil specimens from different geological periods, of which some 750 specimens constitute the fauna of the Cretaceous system that has been the subject of this study; these they have been collected in various localities of the country by the students of the Geological Engineering EAP as part of the field practices, there are also collections made by Rosalvina Rivera, Bernardo Boit, Axel Olsson, Isaac Tafur, among others. The methodology used consisted of the general observation of the fossil samples, taking information about their conservation, numbering, designation, etc., then cleaning and washing each of the fossils was carried out to better observe their external characteristics. The identification of the fossil specimens was then carried out.